Activation of early adenovirus transcription by the herpesvirus immediate early gene: evidence for a common cellular control factor. - Feldman, L T (1982)
Adenovirus mutants carrying a defective E1A gene, such as dl312, are unable to express any of the early viral genes upon infection of HeLa cells. However, efficient expression of the other early adenovirus genes was obtained when dl312-infected HeLa cells were coinfected with pseudorabies virus, a herpesvirus. By employing a temperature-sensitive pseudorabies mutant (tsG1) it was demonstrated that the herpesvirus function responsible for the induction of adenovirus transcription was the immediate early gene, a gene required for the activation of herpesvirus early gene expression and the maintenance of early and late herpesvirus transcription. Specifically, HeLa cells coinfected with dl312 and tsG1, when shifted to the nonpermissive temperature, lost their capacity to express the early adenovirus genes. Furthermore, activation of early adenovirus gene expression in herpesvirus coinfection occurred earlier and at a higher level than in wild-type adenovirus infection. Therefore, the herpesvirus immediate early protein not only activates the early adenovirus transcription units but apparently does so more efficiently than the adenovirus E1A gene product. Because of this fact, we argue that the activation, either by the E1A protein or the herpesvirus immediately early protein, most likely occurs indirectly through interaction with a cellular protein rather than by a direct recognition of regulatory sequences at the adenovirus promoters.